Faktor – Faktor Yang Berhubungan Dengan Kejadian Hipertensi Pada Pasien 45-59 Tahun Di Puskesmas Bintaro Jakarta Selatan Pada Tahun 2022 - Lauren, Gita; Febriyanty, Deasy; Wahidin, Mugi; Heryana, Ade (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
Hypertension is a degenerative disease with a fairly high mortality. Someone who enters the age of 45 years and over will have a higher risk of the incidence of hypertension. Puskesmas Bintaro is a sub-district health center which based on data from the PTM annual report has increased the incidence of hypertension in patients aged 45-59 years from 2019 to 2021. The purpose of this study was to determine the factors associated with the incidence of hypertension in patients aged 45-59 years at the Puskesmas Bintaro, South Jakarta in 2022. The study used a quantitative approach with a Cross Sectional Study design. The independent variables were gender, family history of hypertension, smoking, obesity and sleep quality and the dependent variable was the incidence of hypertension. The data used is primary data in the form of interviews for obesity factors, smoking factors and sleep quality factors. Secondary data is medical record data for hypertension and gender. The sample size in this study was 106 with Quota Sampling collection techniques. The results of this study show that there is a relationship between a family history of hypertension, obesity and sleep quality with the incidence of hypertension at the age of 45-59 years, and shows that there is no relationship between smoking and gender with the incidence of hypertension at the age of 45-59 years. Puskesmas Bintaro also provides counseling about hypertension not only to patients but also to the patient's family. Obesity factor, the Bintaro Health Center can add activities by directly directing patients who are known to be obese to consult the Nutrition Officer at the Puskesmas Bintaro. Sleep Quality Factors Puskesmas Bintaro can add patient sleep quality points to be additional points in patient screening. At this point of sleep quality screening can be done with a short interview.